Dopamine Increases the Intrinsic Excitability of Parvalbumin-Expressing Fast-Spiking Cells in the Piriform Cortex - Potts, Yasmin; Bekkers, John M. (Frontiers in Cellular Neuroscience, 2022)
The piriform cortex (PCx) is essential for the adaptive processing of olfactory information. Neuromodulatory systems, including those utilizing serotonin, acetylcholine, noradrenaline and dopamine, innervate and regulate neuronal activity in the PCx. Previous research has demonstrated the importance of acetylcholine, noradrenaline and serotonin in odor learning and memory. In contrast, the role of dopamine in the PCx remains under-explored. Here we examined how dopamine modulates the intrinsic electrical properties of identified classes of neurons in the PCx. We found that dopamine had no consistent effect on the intrinsic electrical properties of two types of glutamatergic neurons (semilunar and superficial pyramidal cells) or three types of GABAergic interneurons (horizontal, neurogliaform and somatastatin-expressing regular-spiking cells). However, dopamine had a striking effect on the intrinsic excitability of the parvalbumin-expressing fast-spiking (FS) class of GABAergic interneuron. Dopamine depolarized the resting potential, increased the input resistance and increased the firing frequency of FS cells. Co-application of dopamine with the D1-class dopamine receptor antagonist SCH 23390 blocked the effects of dopamine modulation on FS cells. Conversely, co-application of dopamine with the D2-class antagonist RS-(±)-sulpiride had no effect on dopamine modulation of these cells. Our results indicate that dopamine binds to D1-class dopamine receptors to increase the intrinsic excitability of FS cells. These findings suggest that dopamine has a highly targeted effect in the PCx and reveal how dopamine may modulate the balance between excitation and inhibition, with consequences for odor processing. In addition, our findings provide clues for understanding why neurodegenerative disorders that modify the dopamine system, such as Parkinson’s disease, have a deleterious effect on the sense of smell, and may suggest novel diagnostics for the early detection of such disorders.